2015
DOI: 10.1016/s2215-0366(15)00124-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders and suicide attempts in Swedish survivors of the 2004 southeast Asia tsunami: a 5 year matched cohort study

Abstract: Background Survivors of natural disasters are thought to be at an increased risk of psychiatric disorders, however the extent of this risk, and whether it is linked to preexisting psychopathology, is not known. We aimed to establish whether Swedish survivors of tsunamis from the 2004 Sumatra-Andaman earthquake had increased risks of psychiatric disorders and suicide attempts 5 years after repatriation. MethodsWe identified Swedish survivors repatriated from southeast Asia (8762 adults and 3742 children) and 86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…Our results of suicidality risk associated with non-interpersonal trauma (such as natural disaster), only for men, may be due to higher risk of PTSD among men after such trauma. A study by Arnberg et al (2015), for example, found increased risk of PTSD in individuals exposed to the 2004 South-East Asian tsunami compared to unexposed individuals, and that the risk was higher for male survivors [hazard ratio (HR) 11.5, 95% CI 6.77–19.47] than for female survivors (HR 6.30, 95% CI 4.25–9.34). In addition, a study on stressful and traumatic life events found that men had higher levels of PTSD after stressful life events than traumatic events, while women had similar levels of PTSD for both type of events (van den Berg, Tollenaar, Spinhoven, Penninx, & Elzinga, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our results of suicidality risk associated with non-interpersonal trauma (such as natural disaster), only for men, may be due to higher risk of PTSD among men after such trauma. A study by Arnberg et al (2015), for example, found increased risk of PTSD in individuals exposed to the 2004 South-East Asian tsunami compared to unexposed individuals, and that the risk was higher for male survivors [hazard ratio (HR) 11.5, 95% CI 6.77–19.47] than for female survivors (HR 6.30, 95% CI 4.25–9.34). In addition, a study on stressful and traumatic life events found that men had higher levels of PTSD after stressful life events than traumatic events, while women had similar levels of PTSD for both type of events (van den Berg, Tollenaar, Spinhoven, Penninx, & Elzinga, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For some individuals, these experiences are associated with the development of mental health problems such as depression (Mandelli, Petrelli, & Serretti, 2015), substance abuse and stress-related disorders such as posttraumatic stress disorder (PTSD; Arnberg, Bergh Johannesson, & Michel, 2013; Arnberg et al, 2015). However, many individuals experiencing mental health problems after overwhelming events do not receive evidence-based support or treatment (Witteveen et al, 2012), or do not receive treatment until many years after the onset of their problems (Goldstein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…10 To the best of our knowledge, only two studies examining mental health status prior to disaster events have been conducted. 11 12 Both studies suggested that major disaster was associated with an increase in the risk for common…”
Section: Introductionmentioning
confidence: 99%